Are emojis fascinating brand value more than textual language? Mediating role of brand communication to SNS and brand attachment: An insight from India. (8th October 2018) - Arya, Vikas; Sethi, Deepa; Verma, Hemraj
Abstract : Purpose: The purpose of this paper is to understand the relationship of consumers' engagement on social networking sites (SNSs) and their brand attachment behavior in the presence of a mediator, brand communication. Further, this mediation has been studied with presence of emojis as one of the significant moderator. Design/methodology/approach: Following a descriptive research design, an empirical investigation was carried out by approaching 252 respondents from India to collect data through online survey forms as well as physical questionnaires. The research instrument was developed using a five-point Likert-type scale and items for the constructs in study were taken after literature review. The SPSS 22.0, AMOS 24.0 and Process (Prof A. Hayes) and Daniel Soper's statistical tool called "Interaction" for moderation graph were employed for data examination and hypothesis analysis. Findings: It was found that brand communication mediated the relationship between consumer engagement on SNSs and brand attachment significantly. The availability of emojis for a company during a conversation or in digital ad campaigns on SNSs acts as a mediating moderator and its impact on consumers' brand attachment behavior is very strong through brand communication. Originality/value: The study is original in the sense it provides insights into understanding consumer brand attachment behavior on SNSs.